# How to convert from slope intercept to standard form?

#### Understand the Problem

The question is asking for the method to convert an equation expressed in slope-intercept form (y = mx + b) into standard form (Ax + By = C). This involves rearranging the terms and potentially changing their coefficients to meet the standard form requirements.

mx - y = -b

The final standard form of the equation is mx - y = -b

#### Steps to Solve

Begin with the equation in the form $y = mx + b$, where $m$ represents the slope and $b$ represents the y-intercept.

1. Rearrange terms to isolate the $x$ and $y$ terms on one side

Subtract $mx$ from both sides of the equation to move the $x$ term to the left side. This gives: $$y - mx = b$$

1. Rearrange to the standard form structure

Standard form requires the $x$ and $y$ terms on one side and the constant term on the other side. The equation will look like $$-mx + y = b$$

1. Multiply through by -1 if necessary

If the coefficient of $x$ is negative, multiply both sides by -1 to make it positive, resulting in: $$mx - y = -b$$

The final standard form of the equation is mx - y = -b